2016
DOI: 10.1210/en.2015-1872
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S Induces Adipogenesis in Primary Human Preadipocytes From Female Donors

Abstract: Human exposure to bisphenol A has been associated with negative health outcomes in humans and its use is now regulated in a number of countries. Bisphenol S (BPS) is increasingly used as a replacement for bisphenol A; however, its effects on cellular metabolism and potential role as an endocrine disruptor have not been fully characterized. In the current study, we evaluated the effect of BPS on adipogenesis in primary human preadipocytes. The effect of BPS on the differentiation of human preadipocytes was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 50 publications
8
63
0
1
Order By: Relevance
“…12,18 They also have effects on peroxisome proliferator-activated receptor gamma (PPAR) signaling pathway, a main target of obesogens, to increase lipid accumulation and differentiation of preadipocytes into adipocytes. 1921 In addition, BPF could affect adiponectin production and secretion. 18 Moreover, a recent study demonstrated that BPS exposure led to differentially expressed genes related to adipogenesis and lipid metabolism, and it had effects on adipose specific transcriptional changes earlier than BPA.…”
Section: Discussionmentioning
confidence: 99%
“…12,18 They also have effects on peroxisome proliferator-activated receptor gamma (PPAR) signaling pathway, a main target of obesogens, to increase lipid accumulation and differentiation of preadipocytes into adipocytes. 1921 In addition, BPF could affect adiponectin production and secretion. 18 Moreover, a recent study demonstrated that BPS exposure led to differentially expressed genes related to adipogenesis and lipid metabolism, and it had effects on adipose specific transcriptional changes earlier than BPA.…”
Section: Discussionmentioning
confidence: 99%
“…That article also ran a series of experiments blocking several estrogen receptors, which then significantly blocked lipid accumulation. The study went on to propose that BPS is causing lipid accumulation and promoting the differentiation of preadipose cells via the peroxisome proliferator-activated receptor-γ (PPARG) pathway [34]. The second article of that year reported exactly the same results with regard to increased lipid accumulation and several increased adipogenic markers, but they used Murine 3T3-L1 preadipocytes.…”
Section: Dietary Bps Exposure and Obesogenic Effects/metabolic Disordersmentioning
confidence: 94%
“…We and others have previously shown that BPA [ 17 – 20 ] and its metabolite BPA-glucuronide (BPA-G) induce lipid accumulation and adipogenesis in vitro [ 19 ]. Moreover, we have also reported that BPS is adipogenic in human primary preadipocytes, where it induced lipid accumulation and expression of adipogenic genes both at high and at environmentally relevant concentration [ 21 ]. In addition, we and others have shown that BPS treatment increased lipid metabolism, glucose uptake and adipogenesis in the murine 3T3L1 preadipocyte cell line [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%